HEMIN ATTENUATED LPS-INDUCED ACUTE LUNG INJURY IN MICE VIA PROTECTING PULMONARY EPITHELIAL BARRIER AND REGULATING HO-1/NLRP3-MEDIATED PYROPTOSIS. Issue 5 (24th May 2023) - Cheng, Xue; Yin, Mingzhu; Sun, Xiongjie; Zhang, Zhigang; Yao, Xiaowei; Liu, Hongtao; Xia, Hui
ABSTRACT: Pulmonary epithelial barrier injury contributes to acute lung injury, accelerating exudate formation, and resulting alveolar edema. Heme oxygenase-1 (HO-1) plays an important role in ameliorating the pathological symptoms of acute lung injury (ALI). Using an ALI mouse model induced by LPS inhalation, the present study explored the potential molecular regulatory effect of hemin (a potent HO-1 inducer) against ALI epithelial damage. Lipopolysaccharide challenge triggered dysfunction of the alveolar epithelial barrier, impaired tight junctions, and disrupted alveoli fluid clearance, while these pathological changes were effectively reversed by hemin treatment. Furthermore, HO-1 elevation inhibited the activation of the nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome and oxidative stress in alveolar epithelia, leading to the suppression of inflammatory responses and epithelial pyroptosis, as indicated by the decreased levels of NLRP3 and apoptosis-associated speck-like protein containing a CARD domain (ASC), repressed cleavage of caspase-1 and gasdermin D, and reduced expression levels of inflammatory cytokine IL-1β. In contrast, protoporphyrin IX zinc (II) (ZnPP, an HO-1 inhibitor) treatment had no protective effect on LPS inhalation-induced ALI in mice. In summary, HO-1 induction serves a critical role in maintaining airway epithelium homeostasis through the inhibition of NLRP3/ASC/caspase-1–mediated pyroptosis and inflammation in the occurrence of ALI.